Analisis Earning Management Pada Laporan Keuangan Interim Yang Terlambat Publikasi - Nisrina Aisya Kesuma Putri; Tri Joko Prasetyo; Reni Oktavia; Widya Rizki Eka Putri (Jurnal Akuntan Publik, 2024)
Earning management is a practice used by management to change and control earnings, including actions such as adjustments in order to achieve the results desired by management. Earnings management occurs when managers analyze financia staements and make adjustments in recording transactions in the financial statements to mislead stakeholders about the company’s financial performance or influence contractual outcomes that refer to the numbers listed in the financial statements. This action is often carried out by company managers with the intention of manipulating the information contained in the financial statements, so tha stakeholders get a false understanding of the company’s condition or performance. Earning management is divided into two types, namely Accrual Earning Management and Real Earning Management.